OPPORTUNITIES & CHALLENGES WITH AI TECHNOLOGIES IN TEACHER EDUCATION - Kiran Padmaraju (PUPIL: International Journal of Teaching, Education and Learning, 2026)
The emerging AI (Artificial Intelligence) technologies provide both opportunities and challenges for teachers in the classrooms as well as for teacher educators. As a teacher educator for more than twenty years, I have been a witness to the growing technology skills that teacher candidates come with. Unfortunately, some of the misuses of AI technologies are also seen in our courses. Teacher candidates will be surveyed on their outlook towards how AI technologies are going to impact them as a future teacher and how prepared they feel about using AI technologies in their future classrooms. Survey results will be analyzed to consider what AI technologies teacher educators need to model and incorporate in our courses, so teacher candidates improve their sense of self-efficacy with the use of AI technologies. As AI technologies continue to become more available and continue to improve, it is important that the teachers in K-12 classrooms feel more confident in using these technologies to keep their students motivated and engaged in their classrooms. The survey results will inform teacher educators as to what teacher candidates are looking for towards professional growth in AI technologies in their teacher education programs.